Development of penetration zone size prediction technique for hollow-cathode welding technology of spherical titanium tanks - Перерва, Виктор Александрович; Карпович, Елена Владимировна; Федосов, Алексей Викторович (Eastern-European Journal of Enterprise Technologies, 2016)
Implementing the process of hollow-cathode vacuum welding at the plant requires correct mathematical processing of experimental data in order to obtain dependencies of geometrical parameters of the weld on welding conditions. A technique for predicting the geometry of the welded joints obtained by hollow-cathode vacuum welding depending on the welding variables is proposed. The analysis was conducted on samples made of high-strength titanium alloys VT6S. The technique showed that the combined method based on a joint analysis of the results of theoretical and experimental studies allows predicting the geometrical parameters of the penetration zone with a sufficient degree of accuracy. This technique provides a high accuracy of the calculation of the weld sizes in a predetermined range of welding conditions and can be applied in a production environment.